Induksi Enumeratif dan Koherentism dalam sains: Perspektif John Stuart Mill - Rahmadana, Arini; Nahadi; Anwar, Sjaeful (SEARCH: Science Education Research Journal, 2023)
The process of generalisation and the formation of knowledge is often debated about the scientific methods of deduction and induction. There is a dualism between the two. A philosopher of falsification theory, Karl Raymond Popper, criticised induction theory and supported deductive theory, while philosopher John Stuart Mill emphasised the importance of induction in scientific reasoning, especially the use of enumerative induction. In this article, the author tries to briefly explain the urgency of John Stuart Mill's thought in science. Using the library research method, using relevant books and journal articles. Through this research shows the relationship between enumerative induction, coherence and generalisation by John Stuart Mill's can be assembled that enumerative induction shows the consistency pattern of individual cases obtained from repeated observations, where these individual cases in addition to being consistent also have coherence with each other so that a coherent belief system pattern is formed and then forms a generalisation or new science. Although this kind of induction assumption has a level of strength of proof that is difficult to refute. There are still limitations to inductive generalisation, namely the possibility that future discoveries will show that our belief in our current conclusions is incorrect.